General principles of the structure of testes and epididymis in mammals (Texas Journal of Medical Science, 2023)
The reproductive system is a system of organs that is very sensitive and responds to the slightest changes in the body. Therefore, these organs of this system, such as the testes and epididymis, are considered universal organs for experimental research. This article provides data from various sources on the structure of the testes and epididymis in humans and rats.